Catalyst with phthalocyanine-like-metal atom structure as well as preparation method and application of catalyst

By constructing a catalyst with a phthalocyanine-metal atomic structure in situ on active substrate graphene oxide, the problem of thermodynamic instability of single atomic catalysts is solved, efficient catalytic activity and stability are achieved, and production costs are reduced.

CN119746913AActive Publication Date: 2025-04-04WUHAN INST OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411969069.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Due to incomplete surface coordination, existing single-atom catalysts are thermodynamic instability, and are prone to shedding or agglomeration, which affects atomic utilization and catalyst stability.

Method used

A catalyst that is constructed in situ with a phthalocyanine-metal atomic structure on active substrate graphene oxide is formed, and the catalyst is finally obtained by mixing the metal powder with an acidic aqueous solution and ultrasonic reaction, and then adding the precursor solution of graphene oxide, peroxide and nitrogen source to conduct a hydrothermal reaction to form a black hydrogel, and finally obtaining the catalyst by dilute acid treatment.

Benefits of technology

It is achieved that when the molar ratio of the mild hydrogen transfer agent to the aromatic nitro compound is lower than (5-10): 1, the catalyst can still maintain a good yield, and the metal atoms on the surface of the catalyst are evenly dispersed, showing excellent catalytic activity and stability, and reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219086290000081
    Figure BDA0005219086290000081
  • Figure BDA0005219086290000091
    Figure BDA0005219086290000091
  • Figure HDA0005219086300000011
    Figure HDA0005219086300000011
Patent Text Reader

Abstract

The invention discloses a catalyst with a phthalocyanine-like-metal atom structure, and a preparation method of the catalyst comprises the following steps: mixing metal powder and an acidic aqueous solution, carrying out an ultrasonic reaction, then adding the mixture into a precursor solution containing graphene oxide, peroxide and a nitrogen source, carrying out a hydrothermal reaction to obtain black hydrogel, and washing the black hydrogel; and adding the black hydrogel into dilute acid, stirring, and washing to obtain the monatomic catalyst. According to the invention, a phthalocyanine-like-metal atom structure is constructed in situ on the active substrate graphene oxide, so that the electron transmission capability is improved, and the material has excellent catalytic activity and stability, and shows a wide application prospect in the fields of energy conversion, environmental protection, fine chemical engineering and the like; and the related preparation method is simple, the preparation cost of the phthalocyanine structure catalyst can be remarkably reduced, and a new thought is provided for preparation of a high-performance catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalyst with a phthalocyanine-metal atom structure and a preparation method and application thereof. Background Art

[0002] Single-atom catalysts have attracted much attention due to their excellent catalytic effects and high atomic utilization. Research on single-atom catalysts helps to improve catalyst performance and atomic utilization, which is particularly important in the fields of energy conversion and environmental governance. However, single-atom catalysts are usually not thermodynamically stable due to incomplete surface coordination, which makes them more prone to detachment or agglomeration, thus affecting the atomic utilization and stability of the catalyst. To solve this problem, regulating the coordination environment around single metal atoms has become a research hotspot in the field of single-atom catalysis.

[0003] At present, a large number of studies have successfully achieved single-atom anchoring by utilizing the structural characteristics of specific compounds themselves. The prepared single-atom catalysts have the advantages of high selectivity, high activity, and high stability. For example, the catalyst with a stable phthalocyanine structure is synthesized using metal phthalocyanine molecules (Rational design of heterogenized molecular phthalocyanine hybrid single-atom electrocatalyst towards two-electron oxygen reduction, Nature Communication, 2023, 14, 1426); the catalyst with curved active sites is synthesized using nanodiamonds (Meso / microporous single-atomcatalysts with curved Fe-N 4 However, the anchoring of these single atoms is achieved by using specific precursors or endogenous structures. The construction of the coordination environment of metal single atoms is limited by the special molecular structure of the precursor itself or the special morphology of the carrier itself, which makes the preparation strategy of such single-atom catalysts very challenging, such as: (1) the preparation method does not have good universality; (2) it is impossible to accurately control the coordination environment of the single-atom site; (3) the introduced characteristic structure is easily destroyed during the reaction.

[0004] Therefore, it is of great significance to further study the scheme that can construct a stable coordination structure in situ on the active substrate material, rationally regulate the coordination environment around the single atom, reduce the production cost of the single atom catalyst, and improve the stability of the catalyst. Summary of the invention

[0005] The main purpose of the present invention is to provide a catalyst with a phthalocyanine-like metal atom structure in view of the problems and shortcomings of the prior art, in which a phthalocyanine-like metal atom (including iron, cobalt, nickel, etc.) structure is in situ constructed on an active substrate graphene oxide, which can take into account excellent catalytic activity and stability and simplify the preparation process.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A catalyst having a phthalocyanine-metal atom structure, wherein the preparation method comprises the following steps:

[0008] The metal powder is mixed with an acidic aqueous solution and subjected to ultrasonic reaction. After the metal reaction is completed, it is added to a precursor solution containing graphene oxide, peroxide and a nitrogen source, and a hydrothermal reaction is performed to obtain a black hydrogel, which is then washed. The black hydrogel is placed in a dilute acid and stirred, and then washed to obtain the catalyst having a phthalocyanine-metal atom structure.

[0009] In the above scheme, the metal powder is selected from one or more of iron powder, cobalt powder, nickel powder, etc., and the average particle size of the metal powder is 1-10 μm.

[0010] In the above scheme, the acidic aqueous solution is hydrochloric acid, nitric acid or sulfuric acid solution, and its concentration is 1-6 mol / L.

[0011] In the above scheme, the solid-liquid ratio of the metal powder to the acidic aqueous solution is 2 mg: 5-40 μL.

[0012] In the above scheme, the state of the metal reaction being completed is that no granular solid is visible in the aqueous solution to the naked eye.

[0013] Furthermore, the ultrasonic reaction time is 2 to 5 minutes.

[0014] In the above scheme, the nitrogen source can be selected from ammonia water, hydrazine hydrate or hydroxylamine.

[0015] In the above scheme, the peroxide can be hydrogen peroxide, tert-butyl hydroperoxide, peroxyformic acid or peracetic acid water.

[0016] In the above scheme, the mass ratio of the introduced metal powder, graphene oxide, peroxide and nitrogen source is 1:(0.77-10):(1-5.56):(0.1-200).

[0017] In the above solution, the flake diameter of the graphene oxide is 10nm-40μm.

[0018] Furthermore, the precursor solution is a mixture of graphene oxide dispersion, hydrogen peroxide aqueous solution and nitrogen source; the concentration of the graphene oxide dispersion is 3-12 mg / L; the concentration of the peroxide aqueous solution is 0.1-10 wt%; and the concentration of the nitrogen source is 20-30 wt%.

[0019] In the above scheme, the temperature used for the hydrothermal reaction is 160-220° C. and the time is 6-12 hours.

[0020] In the above scheme, the dilute acid can be hydrochloric acid, nitric acid or sulfuric acid aqueous solution, etc., and its concentration is 1-6 mol / L.

[0021] In the above scheme, the mass ratio of the black hydrogel to the dilute acid is 1:1-5.

[0022] In the above scheme, the stirring treatment time is 1-12h, and the rotation speed is 300-800rpm.

[0023] The catalyst with a phthalocyanine-like metal atom structure prepared according to the above scheme has a sheet diameter of nitrogen-doped porous graphene of 10nm-40μm and a porous structure (pore size distribution is 2-10nm); its extended edge X-ray absorption structure is highly similar to that of the phthalocyanine standard sample, and has the advantages of easy electron transfer and stable active intermediates.

[0024] The phthalocyanine-metal atom structure catalyst is applied to the hydrogen transfer reaction of hydrazine hydrate on the aromatic nitro group; a good yield can still be maintained under the condition that the molar ratio of the mild hydrogen transfer agent to the aromatic nitro compound is lower than (5-10):1.

[0025] Furthermore, the mild hydrogen transfer agent may be hydrazine hydrate or the like.

[0026] The present invention uses a small amount of metal element (metal powder) as the metal source, and it is easier to control the size of nanoparticles when in-situ loading is performed on the surface of graphene oxide, and it is easier to achieve precise regulation of the coordination environment of metal single atoms after acid etching.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) Compared with expensive metal phthalocyanine compounds, the present invention uses cheap metal powder as a metal source and anchors it on the active substrate graphene oxide in the form of fine nanoparticles, and promotes the construction of phthalocyanine-like structures, which greatly reduces the production cost of phthalocyanine structure catalysts and provides a new idea for the preparation of high-performance catalysts;

[0029] 2) The metal atoms on the surface of the catalyst of the present invention are evenly dispersed, and can exhibit excellent catalytic activity, and can still maintain a good yield when the molar ratio of the mild hydrogen transfer agent to the aromatic nitro compound is lower than (5-10):1;

[0030] 3) The preparation method involved in the present invention is relatively simple, has good repeatability, is simple to apply, and is suitable for popularization and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a transmission electron microscope image of the iron catalyst obtained in Example 1;

[0032] Figure 2 This is a spherical aberration-corrected scanning transmission electron micrograph of the catalyst obtained in Example 1;

[0033] Figure 3 This is a scan of the energy spectrum of the catalyst obtained in Example 1;

[0034] Figure 4 is the K-edge X-ray absorption near-edge spectrum of the catalyst obtained in Example 1;

[0035] Figure 5 The Fourier transform spectrum of the catalyst obtained in Example 1 is the Fe K edge extended X-ray absorption fine structure spectrum;

[0036] Figure 6 This is a transmission electron microscope image of the nano-iron catalyst obtained in Comparative Example 1;

[0037] Figure 7 Actual photograph of the color change of the solution when the catalyst obtained in Example 1 catalyzes the reduction of p-nitrophenol to p-aminophenol by hydrazine hydrate;

[0038] Figure 8 This is the UV-visible light absorption curve of the solution before and after the catalyst obtained in Example 1 catalyzes the reduction of p-nitrophenol. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] In the following examples, the graphene oxide with a sheet diameter of 10 nm-40 μm was prepared by the modified Hummers method, and the reference is as follows: Preparation of graphic oxide. Journal of the American Chemical Society, 1958, 208, 1334-1339.

[0041] Example 1

[0042] A nitrogen-doped graphene-supported phthalocyanine-iron atomic structure catalyst (Fe 1 -NHG), the preparation method thereof comprises the following steps:

[0043] 20 mg of iron powder with an average particle size of 1 μm was weighed, 160 μL of 6 mol / L hydrochloric acid solution was added, ultrasonicated for 1 min, 200 μL of 3 wt% hydrogen peroxide solution was added, 3.5 mL of deionized water was added after ultrasonication for 30 s, and 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia was added (the introduced graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), and stirred until uniformly dispersed; hydrothermal treatment was performed at 180° C. for 6 h, and the black hydrogel was washed to neutrality. Then, 20 g of the obtained black hydrogel was put into 100 mL of 1 mol / L hydrochloric acid solution and stirred for 12 h (rotation speed is 500 rpm), and washed to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-iron atom structure catalyst.

[0044] The transmission electron microscope image of the catalyst having a phthalocyanine-iron atom structure prepared in this example is shown in FIG. Figure 1 , the microstructure and oxidation etching of graphene can be observed.

[0045] Figure 2 The white bright spots in the spherical aberration-corrected scanning transmission electron microscope represent uniform and isolated single iron atoms with a size of about 2.5 angstroms.

[0046] Figure 3 The energy spectrum of the embodiment 1 proves that the iron single atom catalyst with uniform distribution of each element can be successfully prepared. Figure 4 ,The results show that in the obtained catalyst product, single iron atoms are distributed on the surface of nitrogen-doped graphene in the form of ferrous iron.

[0047] Figure 5 The R spatial analysis of the prepared single-atom catalyst showed that there was no Fe-□Fe bond or Fe-□O bond. At the same time, there were strong signals at 1.5 angstroms and 2.5 angstroms, which were consistent with the signal of the iron phthalocyanine standard sample. The product obtained in Example 1 achieved an R spatial distribution similar to that of the iron phthalocyanine standard sample, and the effective construction of the phthalocyanine-iron atomic structure can be achieved.

[0048] Example 2

[0049] A nitrogen-doped graphene-supported phthalocyanine-iron atomic structure catalyst (Fe 1-NHG), the preparation method thereof comprises the following steps:

[0050] 20 mg of iron powder with an average particle size of 2 μm was weighed, 100 μL of 6 mol / L nitric acid solution was added dropwise, ultrasonicated for 1 min, 200 μL of 3 wt% hydrogen peroxide solution was added, 3.5 mL of deionized water was added after ultrasonication for 30 s, and 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), and stirred until uniformly dispersed; hydroheated at 180° C. for 6 h, washed the black hydrogel to neutrality, and then put 20 g of the obtained black hydrogel into 100 mL of 1 mol / L nitric acid solution and stirred for 12 h (rotation speed is 500 rpm), and washed to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-iron atom structure catalyst.

[0051] Example 3

[0052] A nitrogen-doped graphene-supported phthalocyanine-iron atomic structure catalyst (Fe 1 -NHG), the preparation method thereof comprises the following steps:

[0053] 20 mg of iron powder with an average particle size of 10 μm was weighed, 80 μL of 6 mol / L sulfuric acid solution was added, ultrasonicated for 3 min, 200 μL of 3 wt% hydrogen peroxide solution was added, 3.5 mL of deionized water was added after ultrasonication for 30 s, and 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), stirring until uniform dispersion; hydroheating at 180° C. for 6 hours, washing the black hydrogel to neutrality, and then putting 20.5 g of the obtained black hydrogel into 100 mL of 1 mol / L sulfuric acid solution and stirring for 12 hours (speed is 500 rpm), washing until neutrality and no sulfate radical is contained in the last washing liquid, thereby obtaining a nitrogen-doped graphene-supported phthalocyanine-iron atom structure catalyst.

[0054] Example 4

[0055] A nitrogen-doped graphene-supported phthalocyanine-cobalt atomic structure catalyst (Co 1 -NHG), the preparation method thereof comprises the following steps:

[0056] Weigh 20 mg of cobalt powder with an average particle size of 1 μm, add 160 μL of 6 mol / L hydrochloric acid solution, ultrasonicate for 1 min, add 200 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 3.5 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water in a mass ratio of 1:0.8:40:220), and stirred until uniformly dispersed; hydrothermal treatment was performed at 180° C. for 6 h, the black hydrogel was washed to neutrality, and then 21 g of the obtained black hydrogel was put into 100 mL of a 1 mol / L hydrochloric acid solution and stirred for 12 h (at a rotation speed of 500 rpm), and washed to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-cobalt atomic structure catalyst.

[0057] Example 5

[0058] A nitrogen-doped graphene-supported phthalocyanine-cobalt atomic structure catalyst (Co 1 -NHG), the preparation method thereof comprises the following steps:

[0059] Weigh 20 mg of cobalt powder with an average particle size of 5 μm, add 100 μL of 6 mol / L nitric acid solution, ultrasonicate for 1 min, add 200 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 3.5 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), and stirred until uniformly dispersed; hydroheated at 180° C. for 6 h, washed the black hydrogel to neutrality, and then put 20.2 g of the obtained black hydrogel into 100 mL of 1 mol / L nitric acid solution and stirred for 12 h (rotation speed is 500 rpm), and washed to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-cobalt atomic structure catalyst.

[0060] Example 6

[0061] A nitrogen-doped graphene-supported phthalocyanine-cobalt atomic structure catalyst (Co 1 -NHG), the preparation method thereof comprises the following steps:

[0062] Weigh 20 mg of cobalt powder with an average particle size of 10 μm, add 80 μL of 6 mol / L sulfuric acid solution, ultrasonicate for 3 min, add 200 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 3.5 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), stirring until uniform dispersion; hydroheating at 180° C. for 6 hours, washing the black hydrogel to neutrality, then putting 20.5 g of the obtained black hydrogel into 100 mL of 1 mol / L sulfuric acid solution and stirring for 12 hours (speed is 500 rpm), washing until neutrality and no sulfate radical is contained in the last washing liquid, and thus obtaining a nitrogen-doped graphene-supported phthalocyanine-cobalt atomic structure catalyst.

[0063] Example 7

[0064] A nitrogen-doped graphene-supported phthalocyanine-nickel atomic structure catalyst (Ni 1 -NHG), the preparation method thereof comprises the following steps:

[0065] Weigh 20 mg of nickel powder with an average particle size of 1 μm, add 160 μL of 6 mol / L hydrochloric acid solution, ultrasonicate for 1 min, add 200 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 3.5 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), and stirred until uniformly dispersed; hydrothermal at 180° C. for 6 h, washing the black hydrogel to neutrality, then putting 20.5 g of the obtained black hydrogel into 100 mL of 1 mol / L hydrochloric acid solution and stirring for 12 h (rotation speed is 500 rpm), and washing to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-nickel atomic structure catalyst.

[0066] Example 8

[0067] A nitrogen-doped graphene-supported phthalocyanine-nickel atomic structure catalyst (Ni 1 -NHG), the preparation method thereof comprises the following steps:

[0068] Weigh 20 mg of nickel powder with an average particle size of 1 μm, add 80 μL of 6 mol / L nitric acid solution, ultrasonicate for 1 min, add 200 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 3.5 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), and stirred until uniformly dispersed; hydroheated at 180° C. for 6 h, washed the black hydrogel to neutrality, and then put 20.8 g of the obtained black hydrogel into 100 mL of 1 mol / L nitric acid solution and stirred for 12 h (rotation speed is 500 rpm), and washed to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-nickel atomic structure catalyst.

[0069] Example 9

[0070] A nitrogen-doped graphene-supported phthalocyanine-nickel atomic structure catalyst (Ni 1 -NHG), the preparation method thereof comprises the following steps:

[0071] 20 mg of nickel powder with an average particle size of 10 μm was weighed, 80 μL of 6 mol / L sulfuric acid solution was added, ultrasonicated for 3 min, 200 μL of 3 wt% hydrogen peroxide solution was added, 3.5 mL of deionized water was added after ultrasonication for 30 s, and 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), stirring until uniform dispersion; hydroheating at 180° C. for 6 hours, washing the black hydrogel to neutrality, and then putting 20.3 g of the obtained black hydrogel into 100 mL of 1 mol / L sulfuric acid solution and stirring for 12 hours (speed is 500 rpm), washing until neutrality and no sulfate radical is contained in the last washing liquid, thereby obtaining a nitrogen-doped graphene-supported phthalocyanine-nickel atomic structure catalyst.

[0072] Example 10

[0073] A nitrogen-doped graphene-supported phthalocyanine-like iron-cobalt-nickel triatomic catalyst (FeCoNi-NHG), the preparation method of which comprises the following steps:

[0074] Weigh 20 mg of iron powder, cobalt powder, and nickel powder with an average particle size of 1 μm, add 160 μL of 6 mol / L hydrochloric acid solution, ultrasonicate for 1 min, add 66 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 1.2 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water in a mass ratio of 1:0.8:40:220), stirring until uniformly dispersed; hydroheating at 180° C. for 6 h, washing the black hydrogel to neutrality, then putting 20.1 g of the obtained black hydrogel into 100 mL of 1 mol / L hydrochloric acid solution and stirring for 12 h (at a rotation speed of 500 rpm), washing to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-like iron-cobalt-nickel triatomic catalyst.

[0075] Embodiment 11

[0076] A nitrogen-doped graphene-supported phthalocyanine-like iron-cobalt-nickel triatomic catalyst (FeCoNi-NHG), the preparation method of which comprises the following steps:

[0077] Weigh 20 mg of iron powder, cobalt powder, and nickel powder with an average particle size of 1 μm, respectively, add 80 μL of 6 mol / L nitric acid solution, ultrasonicate for 1 min, add 66 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 1.2 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water in a mass ratio of 1:0.8:40:220), stirring until uniformly dispersed; hydroheating at 180° C. for 6 h, washing the black hydrogel to neutrality, then putting 20 g of the obtained black hydrogel into 100 mL of 1 mol / L nitric acid solution and stirring for 12 h (at a rotation speed of 500 rpm), washing to neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-like iron-cobalt-nickel triatomic catalyst.

[0078] Example 12

[0079] A nitrogen-doped graphene-supported phthalocyanine-like iron-cobalt-nickel triatomic catalyst (FeCoNi-NHG), the preparation method of which comprises the following steps:

[0080] Weigh 20 mg of iron powder, cobalt powder, and nickel powder with an average particle size of 1 μm, add 80 μL of 6 mol / L sulfuric acid solution, ultrasonicate for 1 min, add 66 μL of 3 wt% hydrogen peroxide solution, ultrasonicate for 30 s, add 1.2 mL of deionized water, and add 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water in a mass ratio of 1:0.8:40:220), stirring until uniformly dispersed; hydroheating at 180° C. for 6 h, washing the black hydrogel to neutrality, then putting 20.8 g of the obtained black hydrogel into 100 mL of a 1 mol / L sulfuric acid solution and stirring for 12 h (at a rotation speed of 500 rpm), and washing until neutrality to obtain a nitrogen-doped graphene-supported phthalocyanine-like iron-cobalt-nickel triatomic catalyst.

[0081] Comparative Example 1

[0082] A nitrogen-doped graphene-supported nanoparticle catalyst, the preparation method of which is substantially the same as that of Example 1, except that it is not subjected to dilute acid post-treatment. The specific preparation method is:

[0083] 20 mg of iron powder with an average particle size of 1 μm was weighed, 80 μL of 6 mol / L hydrochloric acid solution was added, ultrasonicated for 1 min, 200 μL of 3 wt% hydrogen peroxide solution was added, and 3.5 mL of deionized water was added after ultrasonication for 30 s, and 26 ml of a mixture of graphene oxide, hydrogen peroxide, and ammonia (graphene oxide, hydrogen peroxide, and NH 3 ﹒ H 2 O and deionized water (mass ratio is 1:0.8:40:220), stirred until uniformly dispersed; hydroheated at 180° C. for 6 h, and finally the black hydrogel (nanoparticulate iron catalyst) was washed to neutrality.

[0084] The transmission electron microscope image of the supported iron catalyst obtained in this comparative example is shown in Figure 6 The average particle size of the nanoparticles is 11.18 nm; it can be seen that the absence of dilute acid etching makes more black particles (iron nanoparticles) distributed on the surface of nitrogen-doped graphene. At this time, the metal utilization rate is low and the cycle stability is poor.

[0085] Application Example 1

[0086] In a 10mL methanol solution of p-nitrophenol (20mmol / L), 40μL of hydrazine hydrate (the molar ratio of hydrazine hydrate to aromatic nitro compound is 5:1) is added, and the solution turns bright yellow. 5mg of the catalyst with a phthalocyanine-like metal structure prepared in Example 1 is added. After 500s, the solution turns colorless, indicating that p-nitrophenol is reduced to generate p-aminophenol. The catalytic effect of the iron single atom catalyst in the catalytic hydrogenation reduction reaction of p-nitrophenol is further verified by ultraviolet-visible absorption spectroscopy. After the catalytic reaction, the characteristic absorption peak of p-nitrophenol disappears, and a new absorption peak of p-aminophenol appears (see Figure 8 ).

[0087] Application Example 2

[0088] In a 10 mL methanol-water mixed solution of p-nitrophenol (20 mmol / L), 378 mg sodium borohydride (50 equivalents) was added, and the solution turned bright yellow. 5 mg of the catalyst obtained in Example 1 was added, and after 180 s, the solution turned colorless (see Figure 7 ), indicating that p-nitrophenol was reduced to form p-aminophenol.

[0089] Application Example 3

[0090] 0.2 mmol of p-nitrobenzoic acid, p-nitrotoluene, p-nitroanisole, p-nitroaniline, p-nitrochlorobenzene, m-nitrochlorobenzene, p-nitrobromobenzene, m-nitrobromobenzene, p-nitrobenzonitrile and nitrobenzene solution were dissolved in 10 mL of methanol, 40 μL of hydrazine hydrate was added, 5 mg of the catalyst obtained in Example 1 was added, and the mixture was heated at 60° C. After a period of time, the product was analyzed by high performance liquid chromatography (HPLC). The obtained product was single and the yield was more than 90%; see Table 1 for details.

[0091] Table 1 Application effect of nitrogen-doped graphene-supported phthalocyanine-like single-atom catalyst of the present invention

[0092]

[0093]

[0094] Application Example 4

[0095] In 10 mL of p-nitrophenol (20 mmol / L) methanol solution, 40 μL of hydrazine hydrate (5 equivalents) was added, and the solution turned bright yellow. 5 mg of the catalyst obtained in Example 1 was added, and after 500 s, the solution turned colorless, indicating that p-nitrophenol was reduced to generate p-aminophenol. The added catalyst was filtered off, washed, dried, and then continued to be added to the same reaction system. After five catalytic cycles, the catalytic time did not decrease significantly.

[0096] In the same reaction system, 5 mg of the nanoparticle iron catalyst prepared in Comparative Example 1 was added. After 500 seconds, the solution became colorless, indicating that p-nitrophenol was reduced to generate p-aminophenol. The added catalyst was filtered out, washed, dried, and then added to the same reaction system. After three catalytic cycles, the catalytic time was extended to 650 seconds, proving that the stability of the nanoparticle iron catalyst prepared in Comparative Example 1 is worse than that of the catalyst with a phthalocyanine-like metal atomic structure prepared in Example 1.

[0097] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a catalyst having a phthalocyanine-metal atom structure, characterized in that: The method comprises the following steps: mixing metal powder with an acidic aqueous solution and subjecting the mixture to ultrasonic reaction, then adding the mixture to a precursor solution containing graphene oxide, peroxide and a nitrogen source, subjecting the mixture to hydrothermal reaction to obtain a black hydrogel, and washing the mixture; The black hydrogel is placed in dilute acid for stirring and washing to obtain the catalyst having a phthalocyanine-metal atom structure.

2. The preparation method according to claim 1, characterized in that: The metal powder is one or more of iron powder, cobalt powder, and nickel powder, and the particle size is 1-10 μm; the acidic aqueous solution is hydrochloric acid, nitric acid or sulfuric acid solution, and the concentration is 1-6 mol / L; the nitrogen source is ammonia water, hydrazine hydrate or hydroxylamine; the peroxide is hydrogen peroxide, tert-butyl hydroperoxide, peroxyformic acid or peracetic acid; the flake diameter of graphene oxide is 10 nm-40 μm.

3. The preparation method according to claim 1, characterized in that: The solid-to-liquid ratio of the metal powder to the acidic aqueous solution is 2 mg:2.5-40 μL.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the introduced metal powder, graphene oxide, peroxide and nitrogen source is 1:(0.77-10):(1-5.56):(0.1-10).

5. The preparation method according to claim 1, characterized in that: The temperature used for the hydrothermal reaction is 160-220° C. and the time is 6-12 hours.

6. The preparation method according to claim 1, characterized in that: The dilute acid is hydrochloric acid, nitric acid or sulfuric acid aqueous solution, and its concentration is 1-6 mol / L.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the black hydrogel to the dilute acid is 1:1-5.

8. The preparation method according to claim 1, characterized in that: The stirring treatment time is 1-12 hours, and the rotation speed is 300-800 rpm.

9. The phthalocyanine-like-metal atom structure catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the phthalocyanine-like metal atom structure catalyst according to claim 9 in the field of hydrogen transfer reaction.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped graphene

    CN104229789A

  • Preparation method for metal nanoparticle-loaded nitrogen-doped porous graphene

    CN106513029A

  • Metal single atom-loaded nitrogen-doped porous graphene composite catalyst and preparation method thereof

    CN111282590A

  • Preparation method of nitrogen-doped graphene-loaded iron-cobalt bimetallic monatomic catalyst

    CN113198507A

  • Model monatomic catalyst and preparation method and application thereof

    CN116393173A